MODEL PENDUGAAN PRODUKSI GONDORUKEM DI DAERAH JAWA TENGAH - Suwidji Basuki; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1990)
Total area of Pine  forests at Perum Perhutani Unit I, Central Java, relatively    enlarges  each year,  but  its utilization for wood  and  resin  tapping  are only  60%. Pine  resin processing of collophonium commodity has yielded  65% in volume. This study  showed  a predictive model  of collophonium  production  at Central Java as Y  = -11,32+0,65X1**-0,43X2 +0,14X3*The  model  above  showed  that Pine resin volume  (X1) is highly  significant  and collophonium  price  (X3)  is significant to collophoniutn  production  (Y),  whereas  labour  variable  (X2) is not  significant because  the  ultilization of  labour is not efficient yet. The simple  regressions Y1 = 28,77 + 0,65 X1 and  Y2 = 1075  + 9,35  X3 are used  to explain  the relation  between Y and X1 or X2 individually.